2014
DOI: 10.3892/mmr.2014.2143
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rac in thromboxane A2-induced human platelet activation: Regulation of sCD40 ligand release and PDGF-AB secretion

Abstract: Abstract.We have previously shown that glycoprotein Ib/IX/V activation stimulates the release of the soluble CD40 ligand (sCD40L) via the generation of thromboxane A 2 from human platelets. In the present study, the role of Rac, which is a member of the Rho family, was investigated in the thromboxane A 2 -stimulated release of platelet-derived growth factor (PDGF)-AB and sCD40L in human platelets. U46619, a thromboxane receptor agonist, stimulated the activation of Rac time-dependently in human platelets, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…HSP27 is a substrate for AKT, and it regulates actin dynamics and degranulation. This confirms the earlier finding that MAPK activation stimulates platelet degranulation and TxA2 synthesis, which may in turn activate platelets via the TP receptor [ 113 ]. After degranulation, soluble factors (ADP, ATP, TxA2, Ca 2+ and thrombin) are released and may act quickly to amplify autocrine activation of platelets as well as the activation of surrounding platelets ( Figure 4 ) [ 88 ].…”
Section: Platelets Cd40l and Molecular Signalingsupporting
confidence: 92%
“…HSP27 is a substrate for AKT, and it regulates actin dynamics and degranulation. This confirms the earlier finding that MAPK activation stimulates platelet degranulation and TxA2 synthesis, which may in turn activate platelets via the TP receptor [ 113 ]. After degranulation, soluble factors (ADP, ATP, TxA2, Ca 2+ and thrombin) are released and may act quickly to amplify autocrine activation of platelets as well as the activation of surrounding platelets ( Figure 4 ) [ 88 ].…”
Section: Platelets Cd40l and Molecular Signalingsupporting
confidence: 92%
“…12 In regard to platelet aggregation, we previously reported that both Rho and Rac are involved in human platelet activation, including PDGF-AB secretion induced by thromboxane A2. 13,14 We also reported that collagen-induced human platelet activation is regulated by Rac. 15 However, the exact mechanism behind the effects of TPO and collagen interactions on platelet activation has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 86%
“…Rho and the downstream effector Rho‐associated kinase (Rho‐kinase) are currently established to play crucial roles in various cellular functions 12 . In regard to platelet aggregation, we previously reported that both Rho and Rac are involved in human platelet activation, including PDGF‐AB secretion induced by thromboxane A2 13,14 . We also reported that collagen‐induced human platelet activation is regulated by Rac 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Rac in human platelets, it has recently been reported that Rac is implicated in platelet aggregation, the activation of α IIb β 3 or phospholipase C, and granule secretion [10][11][12][13]. In our previous report [14], we showed that Rac acts as a positive regulator of the release of soluble CD40 ligand (sCD40L) and the secretion of platelet-derived growth factor-AB (PDGF-AB) induced by TXA 2 from human platelets. Regarding the relationship between PARs and Rac in human platelets, it has been reported that Rac is activated by PAR stimulation [15,16].…”
Section: Introductionmentioning
confidence: 91%